Wizerunek Astrid Lindgren w polskiej prasie - Rogoż, Michał (Acta Universitatis Lodziensis. Folia Librorum, 2010)
Astrid Lindgren’s books are present in the Polish publishing market since late 50’s and enjoy unflagging popularity. Numerous press reports intertwined with successive stages of this literary output. Growing interest in the person of the writer was associated with subsequent jubilees, popular books editions, awards, visits to Poland, and finally with sad news of her death on January 28, 2002. The image of Astrid Lindgren in the Polish media, though not always free of some stereotypes, rush typical of today’s media and pursuit for spectacular news, was authentic in many ways. In those interesting vicissitudes, in many statements by the author herself and in observations made by her close friends could be seen her unique character, self-mockery, optimism, natural vitality and love for children.